Analysis of stack geometry effects on thermoacoustic with particle image velocimetry (PIV) [electronic resource] - Irwan Shah Ali, 1986- (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2011